Hypophosphatemia: Unraveling a Lethal Connection with ICU Mortality in Critically Ill COVID-19 Patients: A Multicenter Observational Study - Temel, Sahin; Hancı, Pervin; Akbudak, İsmail Hakkı and Halaçlı, Burçin and Güven, Göksel and Bilir, Yeliz and Yüksel, Recep Civan and Özyılmaz, Ezgi and Altıntaş, Neriman Defne and Ferliçolak, Leyla and Aydın, Emre and Akbaş, Türkay and Eşbah, Ali Ümit and Güllü, Zuhal and İnci, Kamil and Elay, Gülseren and Topeli, Arzu and Gündoğan, Kürşat (Journal of Medical Biochemistry, 2025)
Abstract Background: Despite a lack of sufficient knowledge about the prevalence and impact of hypophosphatemia in critically ill COVID-19 patients, organ dysfunction, adverse clinical outcomes, and increased mortality have been consistently associated with hypophosphatemia across diverse patient populations. This retrospective, observational study aimed to investigate hypophosphatemia (HypoP) frequency and establish the correlation between variations in serum phosphorus levels and outcomes in critically ill patients with SARS-CoV-2. Methods: The research comprised 205 patients diagnosed with COVID-19 confirmed via RT-PCR. The study included COVID-19 patients who experienced respiratory failure and were in intensive care for more than 24 hours, and their phosphorus values were accurately documented. Clinical parameters, comorbidities, respiratory support requirements, and laboratory findings were analysed. Results: The study participants had a median age of 64 (IQR: 54-75 years), with hypertension being the most prevalent chronic disease (46%). During the first three days of intensive care, 33% of the participants received conventional oxygen support, whereas 54% required intubation and mechanical ventilation (MV). During this period, hypophosphatemia was noted in 25% of patients, with an ICU admission median serum phosphorus level of 1.02 (0.87-1.25) mmol/L. The median duration of stay in the intensive care unit (ICU) was 7 days, significantly extended in patients with hypophosphatemia (p=0.046). Phosphorus levels on the third day of ICU stay were an independent predictor of ICU mortality. (COX, HR= 1.48, 95% CI= 1.11-1.98, p=0.006) Conclusions: During the first three days of ICU admission, 25% of SARS-CoV-2 critically ill adult patients presented with hypophosphatemia. This condition was found to increase ICU mortality rates and prolong ICU stays. Therefore, it is crucial to monitor serum phosphorus levels in the care of critically ill COVID-19 patients.